Produção de celulases utilizando resíduos lignocelulósicos como substrato na fermentação em estado sólido - Cavalcante, Paula Acioly Wanderley (2017)
Vegetable biomass is utilized as a substrate for the production of cellulases since cellulose present in its structure can be converted to a carbohydrate, through fermentation processes, fuel, and other products with high added value. The objective of this work was to study the potential of leaves residues, sugarcane bagasse and corn cob in the production of cellulases from the A. niger fungus by solid-state cultivation. In addition to evaluating an influence of the final concentration of inoculum, initial pH, temperature and moisture in enzymatic and specific activities of total cellulase (FPase) and endoglucanase (CMCase). The fermentation process was carried out with three different residues in Erlenmeyer of 250 mL containing 7,5 g of the substrate with 55% of moisture. The flasks were incubated at 30 °C for 120 h. A 24 factorial design was made with three replications at the central point for the optimization of the cellulase production with the leaves residues, which was maximized from the desirability function. At this stage, the fermentations were carried out in 125 mL Erlenmeyer flasks with 3,5 g of the substrate and incubated for 192 h. The kinetic profile was delineated from the enzymatic and specific activities of total cellulase and endoglucanase, total reducing sugars and microbial growth. The highest enzymatic concentrations for leaves were obtained at 48 and 72 h with 0,78 ± 0,00 U/g for FPase and 1,53 ± 0,01 U/g for CMCase, respectively. For sugarcane bagasse, FPase reached a higher activity in 120 h (1,09 ± 0,01 U/g) whereas the CMCase was higher at 72 h (2,40 ± 0,02 U/g). The corn cob showed higher activity at 120 h for FPase (1,06 ± 0,01 U/g) and at 96 h for CMCase (3,37 ± 0,02 U/g). The specific activities of the leaves residues showed a peak at 48 h (1,29 ± 0,01 U/mgproteins) for FPase and at 72h (1,77 ± 0,01 U/mgproteins) for CMCase. The maximum specific activity of FPase for sugarcane bagasse was 120 h (1,40 ± 0,01 U/mgproteins) and CMCase at 96 h (3,44 ± 0,04 U/mgproteins). Corn cob presented higher specific activities at 72 h for both FPase (1,95 ± 0,35 U/mgproteins) and CMCase (5,84 ± 0,06 U/mgproteins). From the optimization process, the optimal values for enzyme activities were 0,84 U/g to FPase and 1,51 U/g for the CMCase with the overall desirability of 0,96. The optimal points of the specific activities were 4,94 U/mgproteins for FPase and 4,89 U/mgproteins for CMCase with a global desirability of 0,63. The results indicated the capacity of the fungus to produce cellulases in three residues and in short fermentation times, mainly for the leaves. Studied variables influenced the enzymatic and specific activities of FPase and CMCase since their individual or aggregate effects interfered in the microbial growth and the consumption of the substrate, providing a good production of enzymes.